PEMBATALAN MEREK TERKAIT ADANYA PERSAMAAN PADA POKOKNYA DENGAN MEREK TERKENAL - Eno, La Radi; Nurmawati, Bernadete; Santjojo, Eko Suryo (JOS, 2023)
ABSTRACTMarks which cannot be registered and which are rejected, if the Mark is submitted by an Applicant in bad faith, because it is substantially or completely similar to a Mark belonging to another party. In essence, similarities are similarities caused by the presence of dominant elements between one brand and another, giving rise to the impression of similarities, both regarding the shape, method of placement, method of writing or combination of elements, as well as the synchronization of speech sounds contained in the brand. the. In case Number 43/Pdt.Sus-Merek/2019/PNCommerce. Jkt.Pst, the Defendant's